Acupuncture as an adjuvant therapy for management of treatment-related symptoms in breast cancer patients: Systematic review and meta-analysis (PRISMA-compliant). Issue 50 (11th December 2020) - Jang, Soobin; Ko, Youme; Sasaki, Yui; Park, Sunju; Jo, Junyoung; Kang, Na-Hoon; Yoo, Eun-Sil; Park, Nam-Chun; Cho, Seong hee; Jang, Heejea; Jang, Bo-Hyoung; Hwang, Deok-Sang; et al.
Abstract: Background: Although randomized controlled trials have revealed the considerable effectiveness of acupuncture in breast cancer patients, there have been no studies exploring current acupuncture research trends for treatment induced various symptoms in breast cancer patients. This review evaluated the effectiveness of acupuncture for treatment-induced symptoms in breast cancer patients. Methods: We performed a systematic review and meta-analysis of the literature regarding acupuncture to treat symptoms associated with breast cancer therapies. The following databases were searched for relevant RCTs published before June 2018: MEDLINE, EMBASE, the Cochrane Library, AMED, CINAHL, OASIS, CNKI, and CiNii. Results: Among the 19, 483 records identified, 835 articles remained after screening titles and abstracts. A total of 19 RCTs were included in this qualitative synthesis. Among the studies, 8 explored climacteric symptoms, 4 explored pain, 2 explored lymphedemas, 2 explored nausea and vomiting and 3 investigated miscellaneous symptoms. explored miscellaneous symptoms due to cancer treatments. Most of the studies reported that acupuncture can alleviate various symptoms of breast cancer treatment. However, there is a lack of evidence as to whether accupuncture can alleviate chemotherapy associated side effects Conclusions: Acupuncture may alleviate the treatment-related symptoms of breast cancer; however, further studies are necessary to obtain conclusive evidence of the effectiveness of acupuncture in treating breast cancer. Registration number: CRD42018087813